Visualizing Research Trends and Identifying Hotspots of Traditional Chinese Medicine (TCM) Nursing Technology for Insomnia: A 18-Years Bibliometric Analysis of Web of Science Core Collection - Wang, Junxin; Chen, Yufeng; Zhai, Xing; Chu, Yupeng; Liu, Xiangdi; Ma, Xueling (Frontiers in Neurology, 2022)
Objective To explore the research hotspot and frontier direction of TCM nursing of insomnia and provide reference for the follow-up study of the optimal scheme of TCM nursing of insomnia. Background Insomnia is a common sleep-wake disorder, affects 6% to 10% of adults. Benzodiazepines and other treatment have specific side effects. TCM nursing technique of insomnia has a long history and has shown a definite impact. However, it s still lack of analysis in the field of the most commonly used and effective techniques, as well as the co-morbidities associated with insomnia. Thus, this study aims to investigate the research hotspot and frontier direction of TCM nursing techniques in the intervention of insomnia, providing a reference for subsequent research. Method Randomized controlled trials on the intervention of TCM nursing techniques in insomnia were retrieved from Web of Science and imported into CiteSpace 5.6.R5 visualization software. The works of literature were co-cited by keywords authors and institutions for visual analysis, and the co-morbidities associated with insomnia of TCM nursing techniques in literature was extracted manually. The symptoms of co-morbidities associated with insomnia were imported into Cytoscape 3.9.0 software and clustered by CytoHubba. Result The publication period of the included literature was from 2004 to 2021. A total of 146 papers were included, and the highest production year was 2020. There is little cooperation between states, institutions, and authors. China(including Hong Kong and Taiwan) and Hong Kong Polytech University are leading countries and institutions in this area. MYUNGHAENG HUR is the most cited author, and J ALTERN COMPLEM MED is the most cited journal. Auricular therapy, aromatherapy, and acupressure are the three most commonly used techniques, and hemodialysis is the most common co-morbidities associated with insomnia. Conclusion We found that acupressure, aromatherapy and auricular therapy are the most commonly used TCM nursing techniques. However, there are some limits of those research. Therefore, it is necessary to apply objectified sleep quality evaluation methods, select appropriate auricular points according to the theory of TCM, and design a multi-center large-sample clinical trial based on the randomized blind control safety principle.